Study on the characteristics of security and cognitive composition through internet information - Jin Koo, Chang; Yeon Kim, Jeong (International Journal of Engineering and Technology, 2018)
With the increasing ease in which individuals are able to obtain information as a result of the spread of personal networks such as SNS alongside more traditional networks of TV and newspapers, it has become difficult to decipher reliable sources from the unreliable. Yet, when it comes to the question of oversharing information, thus possible data leakage, the question of how individual consumers choose their news sources arises. This paper is interested in building a possible cognitive structure when it comes to how an individual perceives the information from different web platforms.Â